2011
DOI: 10.1111/j.1756-1051.2011.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of Onobrychis shahpurensis (Fabaceae) in Iran, with the description of O. neychalanensis sp. nov.

Abstract: The study of morphology, meiotic behavior, chromosome number and pollen morphology of different populations of Onobrychis shahpurensis Rech. f. (O. sect. Onobrychis) was undertaken to evaluate and determine the variation and circumscription of this species in Iran. All populations were found to be diploid with 2n=2x=14, consistent with the previously proposed base number x=7 for the species. Almost all the populations displayed regular bivalent pairing and chromosome segregation at meiosis. However, some meiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We observed that, at mitosis, the enhancing seed age led to the percentage reduction of the dividing cells. With increasing temperature, the number of cells under division decreases while chromosomal abnormalities and injuries increase, leading, for example, to the formation of anaphase and telophase bridges [65][66][67]. The chromosomal bridge may be caused by chromosomal adhesion and the subsequent inability of chromosomes to initiate a normal anaphase separation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that, at mitosis, the enhancing seed age led to the percentage reduction of the dividing cells. With increasing temperature, the number of cells under division decreases while chromosomal abnormalities and injuries increase, leading, for example, to the formation of anaphase and telophase bridges [65][66][67]. The chromosomal bridge may be caused by chromosomal adhesion and the subsequent inability of chromosomes to initiate a normal anaphase separation.…”
Section: Discussionmentioning
confidence: 99%
“…C). The phenomenon of cytomixis consists in the migration of chromosomes between meiocytes through cytoplasmic connections (Ranjbar et al ). Cytomixis was observed in 11% of telophase I cells and 2.3% of telophase II cells (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens were cross-checked with the various Onobrychis accounts given in the relevant references (Ball, 1968;Hedge, 1970;Grossheim, 1972;Rechinger, 1984;Ranjbar et al, 2007Ranjbar et al, , 2011Ranjbar et al, , 2012Toluei et al, 2012). The new species belonging to sect.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In the Flora Iranica, this section was represented by 14 species (Rechinger, 1984). Recently, Ranjbar et al (2007Ranjbar et al ( , 2009Ranjbar et al ( , 2011Ranjbar et al ( , 2012, Amirabadizadeh (2011), and Toluei et al (2012Toluei et al ( , 2013aToluei et al ( , 2013b Scop., and O. araxina Schischk. as new records.…”
Section: Introductionmentioning
confidence: 99%